Analyzing the Effect of Electronic Word of Mouth towards Future Behavioral Intention of Tourists - DAMAYANTI, Arciana; WIBOWO, Lili Adi; HUMAIRA, Aulian (Journal of Environmental Management and Tourism, 2017)
This study aimed at identifying the effect of Electronic Word of Mouth (EWOM) towards tourists' interest (future behavioral intention) by analyzing the dominant factors which defined EWOM in the scope of social networking sites (SNS). The analysis technique used was partial Least Square (PLS) with samples of 100. Respondents of the study were tourists using the internet as an information source and excursion planning to Langkawi Island, Malaysia. The result of the study showed that there were dominant factors which defined EWOM and that they yielded a weak effect towards future behavioral intention. The push factors and the pull factors from future behavioral intention dimension obtained the highest response from the tourists. The study indicated that EWOM values as a source of information search for planning an excursion trip were very important, but yielded a weak effect towards future behavioral intention, on the grounds that there were still many factors outside EWOM which affected the tourists' interest which require future further studies.